A Virtue for Courageous Minds : Moderation in French Political Thought, 1748-1830. - Craiutu, Aurelian (Princeton University Press, 2012)
Political moderation is the touchstone of democracy, which could not function without compromise and bargaining, yet it is one of the most understudied concepts in political theory. How can we explain this striking paradox? Why do we often underestimate the virtue of moderation? Seeking to answer these questions, A Virtue for Courageous Minds examines moderation in modern French political thought and sheds light on the French Revolution and its legacy. Aurelian Craiutu begins with classical thinkers who extolled the virtues of a moderate approach to politics, such as Aristotle and Cicero.